Construct Analysis of AMDA Model Syntax Using the Structural Equation Modeling-Partial Least Square (SEM-PLS) Method - Sutrisno; Batumahadi Siregar; Riansyah Putra; Nikmat Akmal (Jurnal Penelitian Pendidikan IPA, 2024)
When a building is damaged by an earthquake, it's essential to assess its safety. The AMDA model is the result of the stages of developing a competency-based training model for Post-Earthquake Building Investigation which is designed to make someone competent in this matter. The construct of a development model needs to be tested for validity, reliability and evaluation of the construct or structural model of the syntax of the model being built. Each syntax is confirmed or tested through the value of loadings factor, Average Variance Extracted (AVE) and composite reliability. Next, the influence between variables is analyzed or the structural model or construct (Inner Model) is evaluated. Construct evaluation can be seen from the value of R2 (R-square) between 0 and 1 (0<R2<1), the greater the value and closer to 1, the greater the influence of syntax on the model. The test was carried out using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results obtained were loading factor values>0.7, meaning the indicators used in the syntax were valid, AVE>0.5 meaning the syntax was valid, composite reliability value>0, 7 means the syntax is reliable and the value of R2=0.963, a significant influence of the syntax on the model